The agroecology of an early state: new results from Hattusha. (October 2020) - Diffey, Charlotte; Neef, Reinder; Seeher, Jürgen; Bogaard, Amy
Abstract: Abstract : The discovery of a large underground silo complex with spectacular intact grain stores at the Late Bronze Age Hittite capital of Hattusha in Turkey provides a unique snapshot of the mobilisation of crop production by the Hittite state. A combination of primary archaeobotanical analysis, crop stable isotope determinations and functional weed ecology reveals new insights into Hittite cultivation strategies, featuring a range of relatively low-input, extensive production regimes for hulled wheats and hulled barley. Taxation of extensively produced grain in the sixteenth century BC reveals how an ancient state sought to sustain itself, providing wider implications for the politics and ecology of territorially expansive states in Western Asia and beyond.